Bolt Spacing and End Distance of Bolted Connection of Laminated Veneer Lumber (LVL) Sengon - Ali Awaludin; Dani Nugroho Saputro (Civil Engineering Dimension, 2017)
This paper focuses on bolt connections on Laminated Veneer Lumber (LVL) Sengon. Series of connection tests were conducted to evaluate 3.5d, 5d, and 7d end distances and 3d, 4d, and 5d bolt spacings, where d is a 10 mm bolt diameter. All connections  were double-shear model (steel-LVL-steel). The results showed that all variations of end distance failed in ductile manner especially the connections with end distances of 5d and 7d. Load carrying capacity of the connections with end distances of 5d and 7d were about the same. For single bolt connections, those with 5d bolt spacing had the highest ratio of load carrying capacity. Only the two-bolt connections with 5d bolt spacing gave the ratio of load carrying capacity higher than that of prediction. These findings therefore suggests that minimum end distance of 5d and minimum bolt spacing of 5d are recommended to be addopted in LVL Sengon bolted connections.